2020
DOI: 10.1534/g3.120.401745
|View full text |Cite
|
Sign up to set email alerts
|

The Nuclear Receptor Seven Up Regulates Genes Involved in Immunity and Xenobiotic Response in the AdultDrosophilaFemale Fat Body

Abstract: The physiology of organisms depends on inter-organ communication in response to changes in the environment. Nuclear receptors are broadly expressed transcription factors that respond to circulating molecules to control many biological processes, including immunity, detoxification, and reproduction. Although the tissue-intrinsic roles of nuclear receptors in reproduction have been extensively studied, there is increasing evidence that nuclear receptor signaling in peripheral tissues can also influence oogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 103 publications
(139 reference statements)
0
9
0
Order By: Relevance
“…Besides HR96, Seven up (Svp), another nuclear hormone receptor in D. melanogaster, was newly reported also related to the expression of several detoxification genes. When svp was knocked down in the adult fat body, the expression of Cyp12d-1, Cyp4e3, Cyp4p2, and GstD5 was clearly reduced (Weaver & Drummond-Barbosa, 2020). However, whether Svp plays a role in induced expression of these targets after toxin contaction, is still an open question about the role of Svp in xenobiotic response exist.…”
Section: The Hr96 Pathwaymentioning
confidence: 99%
“…Besides HR96, Seven up (Svp), another nuclear hormone receptor in D. melanogaster, was newly reported also related to the expression of several detoxification genes. When svp was knocked down in the adult fat body, the expression of Cyp12d-1, Cyp4e3, Cyp4p2, and GstD5 was clearly reduced (Weaver & Drummond-Barbosa, 2020). However, whether Svp plays a role in induced expression of these targets after toxin contaction, is still an open question about the role of Svp in xenobiotic response exist.…”
Section: The Hr96 Pathwaymentioning
confidence: 99%
“…Work in Drosophila has illustrated how signals from fat tissue can modulate mTOR signaling within germline stem cells ( Armstrong et al, 2014 ). Subsequent studies from the Drummond-Barbosa lab have continued to characterize how interorgan communication influences germ cell development in flies ( Matsuoka et al, 2017 ; Armstrong and Drummond-Barbosa, 2018 ; Weaver and Drummond-Barbosa, 2018 , 2019 , 2020 , 2021 ). Work from the Conti and Eppig labs, among others, shows that bidirectional communication between developing oocytes and their somatic cell neighbors also plays an important role in mammalian germ cell development ( Chen et al, 2013 ; Wigglesworth et al, 2013 ).…”
Section: Regulation Of Translation Machinery During Germ Cell Developmentmentioning
confidence: 99%
“…Recently, Weaver and Drummond-Barbosa showed that the nuclear receptor Svp regulates a number of factors involved in immunity and xenobiotic detoxification responses in adult female FB ( Weaver and Drummond-Barbosa, 2020 ). Specifically, Svp would acts as the first line of defence against infections, regulating genes involved in the capture and elimination of foreign pathogens.…”
Section: Role Of Adult Fat Bodymentioning
confidence: 99%
“…Svp also regulates the expression of genes encoding members of the CYP450 family involved in the initiation of phase I of the xenobiotic detoxification response. Reduction of svp expression results in the upregulation of genes encoding Metallothionein A and B ( MtnA and MtnB ) ( Weaver and Drummond-Barbosa, 2020 ). MtnA and B are enzymes involved in heavy metal detoxification and protection against free radicals and have been involved in the response to xenobiotic and immune stress ( Bonneton et al, 1996 ).…”
Section: Role Of Adult Fat Bodymentioning
confidence: 99%
See 1 more Smart Citation